2020
DOI: 10.3390/polym12112678
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Bio-Based Gelatin Sponge for Potential Use as A Functional Acellular Skin Substitute

Abstract: Gelatin possesses biological properties that resemble native skin and can potentially be fabricated as a skin substitute for full-thickness wound treatment. The native property of gelatin, whereby it is easily melted and degraded at body temperature, could prevent its biofunctionality for various applications. This study aimed to fabricate and characterise buffalo gelatin (Infanca halal certified) crosslinked with chemical type crosslinker (genipin and genipin fortified with EDC) and physicaly crosslink using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…An X-ray diffractogram has shown a broad peak for both NC_GH and GNP_GH which indicated their amorphous nature characteristic [ 58 ]. Those findings suggested that GNP modification did not significantly alter gelatin’s natural conformation and was consistent with previous results that have been demonstrated by Arif et al [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…An X-ray diffractogram has shown a broad peak for both NC_GH and GNP_GH which indicated their amorphous nature characteristic [ 58 ]. Those findings suggested that GNP modification did not significantly alter gelatin’s natural conformation and was consistent with previous results that have been demonstrated by Arif et al [ 55 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, GH is usually featured by low gel strength without any modifications [ 48 , 52 ]. Hence, GNP crosslinking is an essential approach to improve the mechanical strength by creating an intermolecular bridge between gelatin molecules through the covalent bond [ 24 , 55 ]. Thus, they also have demonstrated reasonable resilient and adhesive force properties.…”
Section: Discussionmentioning
confidence: 99%
“…In pressure ulcers, amazing recovery was seen in HVMPC [84][85][86]103]. The outcome of ES was comparable to the negative pressure wound therapy (NPWT) in a study of pressure ulcers [104].…”
Section: Types Of Cellmentioning
confidence: 91%
“…Gelatin is a partially hydrolyzed version of collagen and retains most collagen chemical functionality [ 78 ]. It is composed of triple amino acids of glycine proline and hydroxyproline and has been added to various biomaterials to enhance cell scaffold interactions through its Arginine-Glycine-Aspartic acid sequences, which are easily recognized by integrin receptors of cell membranes [ 81 ]. Gelatin nanofibers, along with several scaffolds like gelatin alginate sponges, gelatin-containing EGF, and gelatin films, showed possible applications in the treatment of burnt skin healing and regeneration [ 78 ].…”
Section: Components Of Skin Tissue Engineering and Regenerative Medicinementioning
confidence: 99%